Construction of Basic Scholar Device For Education Proces and For Electro-Chemical Analysis of Solutions - ADÁMEK, PETR (Journal of Education, Technology and Computer Science, 2018)
The article deals with construction of electronics device usable in teaching process of tech-nology education. The device is applicable in teaching of programming. Produced activated and tested scholar device is capable make the electro – chemical analysis of liquid solutions. This kind of observation is required in ecology.